Dinamika Kekuasaan Dalam Penyelesaian Konflik Antar Agama - Rohmah, Elva Imeldatur (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2023)
This article attempts to address issues related to power asymmetry in the resolution of interreligious conflicts and the mechanisms used to resolve such conflicts. The research is conducted using a qualitative approach with a descriptive-analytical method. The state has an important role in resolving inter-religious conflicts through public policies involving legislation, law enforcement, promotion of inter-religious dialogue, and protection of human rights. In the resolution of interreligious conflicts, there is often a power asymmetry between the involved religious groups. Power asymmetry refers to the imbalance of political, economic, or social power between conflicting religious groups. This imbalance can influence the dynamics of conflict resolution and create challenges that need to be overcome. Common mechanisms used in the resolution of interreligious conflicts include interfaith dialogue, reconciliation, mediation, and a restorative justice approach. In the resolution of interreligious conflicts, each mechanism has its own uniqueness and advantages.